Hubungan antara Self-Efficacy dan Dukungan Sosial dengan Coping Stress pada Petani Hortikultura dalam Mengelola Usaha Tani di Saribudolok - Sabrina Agrivita Saragih; Asih Menanti; Zuhdi Budiman (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2020)
The purpose of this study is to see the relationship between self-efficacy and social support with coping stress on horticulture farmers. The study was conducted in Saribudolok sample random sampling with 160 horticultural farmers for vegetable farmers as sample. The methods of data collections is through coping stress scale (focused coping stress), self-efficacy scale, and social support scale (sosial support). The data analysis technique used multiple regression with the following results: 1) There is a positive relationship between self-efficacy with coping stress with Rxy = 0,464 with p 0,05; with 21.6% contribution 2) There is a positive relationship between social support relationship with coping stress with Rxy = 0,180 with p 0,05; with 3.2% contribution 3) There is a positive relationship between self-efficacy and social support with coping stress with F 23,072 and Rxy = 0,477 while R2 = 0,227 with p 0,05. The total effective contribution of self-efficacy variables and social support with stress coping is 22.7%. This means that there is still 77.3% influence from other factors to coping stress